2006
DOI: 10.1111/j.1420-9101.2006.01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Changed environmental conditions weaken sexual selection in sticklebacks

Abstract: Environmental heterogeneity can cause the intensity and direction of selection to vary in time and space. Yet, the effects of human‐induced environmental changes on sexual selection and the expression of mating traits of native species are poorly known. Currently, the breeding habitats of the three‐spined sticklebackGasterosteus aculeatus are changing in the Baltic Sea because of eutrophication and increased growth of algae. Here we show that enhanced growth of filamentous algae increases the costs of mating b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
173
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(178 citation statements)
references
References 55 publications
2
173
2
1
Order By: Relevance
“…For example, spatial variation in the risk of predation affects both male secondary sexual characters and female preference functions (Stoner & Breden 1988;Houde & Endler 1990). Similarly, sustained temporal change driven by human-induced climate change or pollution affects both signalling and sexual selection ( Järvenpää & Lindström 2004;Møller 2004;Spottiswoode et al 2006;Candolin et al 2007). In addition, the signal can depend more on the early environmental conditions than the underlying genotype (Griffith et al 1999;Qvarnströ m 1999;Jensen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, spatial variation in the risk of predation affects both male secondary sexual characters and female preference functions (Stoner & Breden 1988;Houde & Endler 1990). Similarly, sustained temporal change driven by human-induced climate change or pollution affects both signalling and sexual selection ( Järvenpää & Lindström 2004;Møller 2004;Spottiswoode et al 2006;Candolin et al 2007). In addition, the signal can depend more on the early environmental conditions than the underlying genotype (Griffith et al 1999;Qvarnströ m 1999;Jensen et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a reduction in the efficacy of sexual signals of many taxa due to human‐induced environmental change (reviewed in Lürling & Scheffer, 2007). For example, massive algae growth related to eutrophication increased the time and energy spent by Gasterosteus aculeatus males in courtship, while at the same time, relaxed the strength of selection in the male red courtship coloration (Candolin, Salesto, & Evers, 2007). Similarly, increased volatility and reduced permanency of scent marks may decrease the information that receivers can gain from chemical signals, reducing their ability to assess male quality (Martín & López, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is also plausible that the yellow coloration exhibited by fishes inhabiting the most red optical conditions simply reflects lowered investment in signal production. Disruptive transmission environments can relax selection on sexual signal production [46,47]. If the transmission environment is antagonistic to effective signalling, investment in signal production may constitute a substantial fitness cost [48] which could explain the predominance of yellow signals (i.e.…”
Section: Discussionmentioning
confidence: 99%